Analysis of factors that influence the PAH profile and amount in meat products subjected to thermal processing. (September 2021) - Onopiuk, Anna; Kołodziejczak, Klaudia; Szpicer, Arkadiusz; Wojtasik-Kalinowska, Iwona; Wierzbicka, Agnieszka; Półtorak, Andrzej
Abstract: Background: Polycyclic aromatic hydrocarbons (PAHs) are organic food contaminants of natural or anthropogenic origin, and are considered carcinogenic and mutagenic. Thus, their content in food products must be controlled. PAHs can be formed as by-products of technological processes e.g., smoking and grilling. Scope and approach: The analysis of scientific studies and technological solutions enabled identification of factors that influence PAHs profile and content in products subjected to thermal processing. The objective of this paper was to examine the various possibilities of optimization of technological solutions that could reduce the risk of PAHs formation in food. Key findings and conclusion: The presented strategies for reduction of PAHs contamination in meat includes modification of the process parameters and methods of handling the half products and ready products. Reduction of PAHs levels in smoked or grilled products can be achieved using the appropriate fuel, placing the product at a greater distance from the heat source or using a barrier between the heat source and product, reducing the duration and temperature of the thermal treatment, and choosing products with lower fat content and preparing them appropriately e.g. by wrapping or using additives that reduce the formation of PAHs such as marinates with acidic pH that contain phenolic compounds. Highlights: Thermal processing parameters affect the PAH content in smoked and grilled products. Natural casing and high fat content increase the PAH content in the product. Wrapping, pre-heating and marinating may decrease the PAH content in the product. Optimization of technological solutions can reduce the risk of PAH formation in food.